Impact of prenatal maternal cytokine exposure on sex differences in brain circuitry regulating stress in offspring 45 years later - Goldstein, Jill M; Cohen, Justine E; Mareckova, Klara; Holsen, Laura; Whitfield-Gabrieli, Susan; Gilman, Stephen E; Buka, Stephen L; Hornig, Mady (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Stress is associated with numerous chronic diseases, beginning in fetal development with in utero exposures (prenatal stress) impacting offspring's risk for disorders later in life. In previous studies, we demonstrated adverse maternal in utero immune activity on sex differences in offspring neurodevelopment at age seven and adult risk for major depression and psychoses. Here, we hypothesized that in utero exposure to maternal proinflammatory cytokines has sex-dependent effects on specific brain circuitry regulating stress and immune function in the offspring that are retained across the lifespan. Using a unique prenatal cohort, we tested this hypothesis in 80 adult offspring, equally divided by sex, followed from in utero development to midlife. Functional MRI results showed that exposure to proinflammatory cytokines in utero was significantly associated with sex differences in brain activity and connectivity during response to negative stressful stimuli 45 y later. Lower maternal TNF-α levels were significantly associated with higher hypothalamic activity in both sexes and higher functional connectivity between hypothalamus and anterior cingulate only in men. Higher prenatal levels of IL-6 were significantly associated with higher hippocampal activity in women alone. When examined in relation to the anti-inflammatory effects of IL-10, the ratio TNF-α:IL-10 was associated with sex-dependent effects on hippocampal activity and functional connectivity with the hypothalamus. Collectively, results suggested that adverse levels of maternal in utero proinflammatory cytokines and the balance of pro- to anti-inflammatory cytokines impact brain development of offspring in a sexually dimorphic manner that persists across the lifespan.
Keywords: dospělí; Magnetic Resonance Imaging; Female; Connectome; Cytokines; Adult; ženské pohlaví; psychický stres; cytokiny; lidé; magnetická rezonanční tomografie; těhotenství; zpožděný efekt prenatální expozice; prenatal immune programming; sex; konektom; prenatal stress; Sex Factors; Hypothalamus; Male; sexuální faktory; hypothalamus; Prenatal Exposure Delayed Effects; functional brain imaging; stress circuitry; mužské pohlaví; Pregnancy; Stress, Psychological; Humans